The arrhythmic substrate of hypertrophic cardiomyopathy using ECG imaging - Chow, Ji-Jian; Leong, Kevin M. W.; Shun-Shin, Matthew; Jones, Sian; Guttmann, Oliver P.; Mohiddin, Saidi A.; Lambiase, Pier; Elliott, Perry M.; Ormerod, Julian O. M.; Koa-Wing, Michael; Lefroy, David; Lim, Phang Boon; et al. (Frontiers in Physiology, 2024)
Patients with hypertrophic cardiomyopathy (HCM) are at risk of lethal ventricular arrhythmia but the electrophysiological substrate behind this is not well understood. We used non-invasive electrocardiographic imaging to characterize patients with HCM, including cardiac arrest survivors. HCM patients surviving ventricular fibrillation or hemodynamically unstable ventricular tachycardia (n=17) were compared to HCM patients without a personal history of potentially lethal arrhythmia (n=20) and a pooled control group with structurally normal hearts. Subjects underwent exercise testing with non-invasive electrocardiographic imaging to estimate epicardial electrophysiology. Visual inspection of reconstructed epicardial HCM maps revealed isolated patches of late activation time (AT), prolonged activation recovery intervals (ARI), as well as reversal of apico-basal trends in T wave inversion and ARI compared to controls (p<0.005 for all). AT and ARI were compared between groups. The pooled HCM group had longer mean AT (60.1ms vs 52.2ms, p<0.001), activation dispersion (55.2ms vs 48.6ms, p=0.026), and mean ARI (227ms vs 217ms, p=0.016) than normal heart controls. HCM ventricular arrhythmia survivors could be differentiated from HCM patients without personal history of life-threatening arrhythmia by longer mean AT (63.2ms vs 57.4ms, p=0.007), steeper activation gradients (0.45ms/mm vs 0.36ms/mm, p=0.011), and longer mean ARI (234.0ms vs 221.4ms, p=0.026). A logistic regression model including whole heart mean activation time and activation-recovery interval could identify the ventricular arrhythmia survivors from the HCM cohort, producing a C-statistic of 0.76 (95% confidence interval 0.72-0.81), with optimal sensitivity 78.6% and specificity of 79.8%. The HCM epicardial electrotype is characterized by delayed, dispersed conduction and prolonged, dispersed activation-recovery intervals. Combination of electrophysiologic measures by logistic regression can improve differentiation over single variables. Future studies could test such models prospectively for risk stratification of sudden death in HCM.